THE STUDY OF THE LUMINESCENCE PROPERTIES OF Y0.85‑ xYb0.15Er x Al3(BO3)4 - Sergey Vladimirovich Kostyukov; Viktor Andreevich Vorobyev (Вестник Северо-Кавказского федерального университета)
Has established the dependence of the intensity of Stokes IR-luminescence of polydisperce solid solutions Y0.85‑xYb0.15ErxAl3(BO3)4 at 800–2000 nm under laser excitation 940–980 nm from the composition. Has identified optimal composition of the phosphor Y0.85‑xYb0.15ErxAl3(BO3)4.